Performance of an Adaptive Controller for the Neuromuscular Blockade Based on Inversion of a Wiener Model. Issue 4 (10th September 2014) - Silva, M. M.; Paz, L.; Wigren, T.; Mendonça, T.
Abstract An adaptive controller based on a minimally parameterized parsimonious Wiener model for the effect of the muscle relaxant rocuronium in the neuromuscular blockade is presented. The controller structure combines inversion of the recursively identified static nonlinearity of the Wiener model with a positive compartmental control law for the linearized system. The overall strategy exploits the fact that the model has only two parameters, which are estimated by an extended Kalman filter. Due to the fact that the positive control law for total mass conservation of compartmental systems is only proven to be convergent for time‐invariant systems, the identification of the parameter in the linear block of the minimally parameterized parsimonious Wiener model is stopped when the controller is turned on. The controller was implemented in the platform Galeno and tested in simulation and in thirteen real cases of patients under general anesthesia. The good reference tracking results and robustness to noise show the reliability of the proposed strategy.